2009
DOI: 10.1103/physrevb.79.014109
|View full text |Cite
|
Sign up to set email alerts
|

Tight-binding potential for atomistic simulations of carbon interacting with transition metals: Application to the Ni-C system

Abstract: We present a tight-binding potential for transition metals, carbon, and transition metal carbides, which has been optimized through a systematic fitting procedure. A minimal basis, including the s, p electrons of carbon and the d electrons of the transition metal, is used to obtain a transferable tight-binding model of the carbon-carbon, metal-metal and metal-carbon interactions applicable to binary systems. The Ni-C system is more specifically discussed. The successful validation of the potential for differen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
116
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(124 citation statements)
references
References 138 publications
6
116
0
2
Order By: Relevance
“…This was used to study these systems at 1000 or 1500 K and provides good statistics for a variety of SWNT chiralities and initial distributions of the Ni atoms. This TB Hamiltonian has been developed specifically for nickel-carbon systems [13], and has been successfully used by Amara et al [12] to study the formation of graphitic carbon structures on Ni surfaces and clusters. Their study showed that solubility of carbon atoms in nickel is limited, but that carbon atoms are also stable at subsurface sites.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was used to study these systems at 1000 or 1500 K and provides good statistics for a variety of SWNT chiralities and initial distributions of the Ni atoms. This TB Hamiltonian has been developed specifically for nickel-carbon systems [13], and has been successfully used by Amara et al [12] to study the formation of graphitic carbon structures on Ni surfaces and clusters. Their study showed that solubility of carbon atoms in nickel is limited, but that carbon atoms are also stable at subsurface sites.…”
Section: Methodsmentioning
confidence: 99%
“…Simulations of the SWNT-Ni systems are based on a fourth moment TB approximation [12] combined with canonical MC [15]. This was used to study these systems at 1000 or 1500 K and provides good statistics for a variety of SWNT chiralities and initial distributions of the Ni atoms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found that for curved structures, the formation of Ni-C bonds is more efficient, and that C atoms prefer to be located in semioctahedral sites of Ni present on the surface. Amara et al [31] presented a model based on approximations, which provided an efficient tool to calculate the bonding energies in the Ni-C system and investigated the variation of the calculated energy of dissolution with the size of super cell. This model can be easily generalized to other metalcarbon systems.…”
Section: Discrete Computational Modelingmentioning
confidence: 99%
“…The microscopic images of CNTs growing upon the catalytic nanoparticles [4] help to clarify how the models of the Me-CNT junction can be drawn. The optimal performance of carbon nanotubes requires control of their structural properties [5], , size, length, chirality, which remains a significant difficulty for the widespread application of CNTs in high-technology devices. The formation of SW CNTs mainly requires the presence of transition-metal element or alloy catalysts (Co, Ni, Fe, Y, etc.…”
Section: Introductionmentioning
confidence: 99%